Focus on periodontal engineering by 3D printing technology - A systematic review. - Manchala Sesha Reddy; Shishir Ram Shetty; Raghavendra Manjunath Shetty; Venkataramana Vannala; Shakeel Sk; Rajasekar S (Universidad de Concepción., 2020)
Three-dimensional (3D) bioprinting of cells is an emerging area of research but has not been explored yet in the context of periodontal tissue engineering. Objetive: This study reports on the optimization of the 3D bioprinting scaffolds and tissues used that could be applied clinically to seniors for the regenerative purpose to meet individual patient treatment needs. Material and Methods: We methodically explored the printability of various tissues (dentin pulp stem/progenitor cells, periodontal ligament stem/progenitor cells, alveolar bone stem/progenitor cells, advanced platelet-rich fibrin and injected platelet-rich fibrin) and scaffolds using 3D printers pertaining only to periodontal defects. The influence of different printing parameters with the help of scaffold to promote periodontal regeneration and to replace the lost structure has been evaluated. Results: This systematic evaluation enabled the selection of the most suited printing conditions for achieving high printing resolution, dimensional stability, and cell viability for 3D bioprinting of periodontal ligament cells. Conclusion: The optimized bioprinting system is the first step towards the reproducible manufacturing of cell laden, space maintaining scaffolds for the treatment of periodontal lesions.